2017
DOI: 10.3889/oamjms.2017.193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Adding Pioglitazone or Sitagliptin to Patients with Type 2 Diabetes Mellitus Insufficiently Controlled With Metformin

Abstract: BACKGROUND:Diabetes mellitus is a progressive disorder that often requires combination therapy.AIM:This study aimed to compare and study of add-on sitagliptin versus pioglitazone in patients with type 2 diabetes inadequately controlled with metformin.METHODS:This 12-week, randomised, open-label and single centre study compared sitagliptin (100 mg daily, n = 80) and pioglitazone (30 mg daily, n = 80) in type 2 diabetic patients whose disease was not adequately controlled with metformin.RESULTS:The mean change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Similarly, Khaloo et al (7) reported that sitagliptin and pioglitazone had similar effects on the level of HbA1c. Jameshorani et al (20) also reported the similar effects of sitagliptin and pioglitazone in combination with metformin on the improvement of HbA1c. In addition, Liu et al (13) indicated the effectiveness of sitagliptin and pioglitazone in the reduction of HbA1c level; nonetheless, a greater FBS reduction was observed in response to pioglitazone, compared to that reported for sitagliptin.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, Khaloo et al (7) reported that sitagliptin and pioglitazone had similar effects on the level of HbA1c. Jameshorani et al (20) also reported the similar effects of sitagliptin and pioglitazone in combination with metformin on the improvement of HbA1c. In addition, Liu et al (13) indicated the effectiveness of sitagliptin and pioglitazone in the reduction of HbA1c level; nonetheless, a greater FBS reduction was observed in response to pioglitazone, compared to that reported for sitagliptin.…”
Section: Discussionmentioning
confidence: 81%
“…Findings regarding the comparative effects of the drugs on HbA1c reduction are mixed, with some studies reporting that pioglitazone was superior to sitagliptin, [21][22][23] and others not supporting this finding. [24][25][26] Reasons for these inconsistent findings may include different pioglitazone dosages, different drug combinations, and varying treatment durations. However, results specific to body weight change, tolerability, and safety profiles were quite consistent.…”
Section: Previous Findings Comparing Pioglitazone and Sitagliptinmentioning
confidence: 99%
“…Specifically, these studies reported that pioglitazone was inferior to sitagliptin in terms of weight control, and both drugs were generally well tolerated. [21][22][23][24][25][26] noting that none of the studies based their conclusion on patients with T2D from mainland China. A propensity score-matched analysis found that compared with DPP4 inhibitors, TZD was significantly better at alleviating IR and inferior at improving β cell function.…”
Section: Previous Findings Comparing Pioglitazone and Sitagliptinmentioning
confidence: 99%